Hadith #2436 - Sunan Abi Dawud - al-Hur bin al-Sabah الحر بن الصباح النخعي; Hunayda bin Khalid; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The client of Usamah ibn Zayd said that he went along with Usamah to Wadi al-Qura in pursuit of his camels. He would fast on Monday and Thursday. His client said to him: Why do you fast on Monday and Thursday, while you are an old man? He said: The Prophet of Allah (ﷺ) used to fast on Monday and Thursday. When he was asked about it, he said: The works of the servants (of Allah) are presented (to Allah) on Monday and Thursday.
Grade: Sahih